Analisis Bibliometrik Vosviewer Tutor Sebaya sebagai Learning Organization dalam Pembelajaran - Sumarni, Ria Asep; Dadi, Kanisius Komsiah; Japar, Muhammad; Herdiati, Dian (Universitas Indraprasta PGRI Jakarta, 2024)
Several studies on peer tutoring can be analyzed within the framework of learning organization implementation. This study aims to evaluate the role of peer tutoring in education through a bibliometric analysis approach. Using the VOSviewer software, this research identifies and maps the relationships between various concepts related to peer tutoring and Learning Organization. Data was collected in POP using the keyword